1977
DOI: 10.1103/physrevc.16.1146
|View full text |Cite
|
Sign up to set email alerts
|

Production,Lx-ray identification, and decay of the nuclide105260

Abstract: The nucljde 105 has been produced jn the Cf(' N, 4') reaction and its docay properties investigated. The a-decay branch of 1.52~0.13-sec ' 105 has been measured to be (90.4~0.6)% with spontaneous-fission decay the remainder [(9. 6+0.6)%]. Measured a-particle energies and intensities (% per decay) are 9.041+ 0.014 MeV (48 + 5), 9.074~0.014 MeV (25 + 3), and 9.120 + 0.017 MeV (17 + 3). Characteristic Lseries x rays of element 103 were observed in coincidence with these a-particle groups, thus providing elemental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…The energy agrees with the value reported for the low energy line of 257 Lr [19]. 8870 keV: About 10% of the events contributing to this energy, which was previously assigned to 257 Lr [18,19], are correlated to 253 No. We thus interprete this line as a mixture of 257 Lr and 257 104.…”
Section: Isotope 257 104supporting
confidence: 81%
See 2 more Smart Citations
“…The energy agrees with the value reported for the low energy line of 257 Lr [19]. 8870 keV: About 10% of the events contributing to this energy, which was previously assigned to 257 Lr [18,19], are correlated to 253 No. We thus interprete this line as a mixture of 257 Lr and 257 104.…”
Section: Isotope 257 104supporting
confidence: 81%
“…8636 keV: none of the 16 events observed is correlated to 253 No. Therefore this line cannot be attributed to 257 104. α-decay energies close to this value are known for 258 Lr [18,19] and for 256 Lr [19], yet an assignment to any of these nuclei was not likely. 258 Lr cannot be produced directly in that reaction, since its neutron number is by one higher than that of the compound nucleus 258 104.…”
Section: Isotope 257 104mentioning
confidence: 80%
See 1 more Smart Citation
“…Unfortunately, the quality of the alpha data is poor and even in 1971 papers by Druin ef nl. [39] >258~r (a, 3.9s These results were later confirmed by Bemis et al [42], using an L X-ray-alpha coincidence technique.…”
Section: Hahnium (Element 105)supporting
confidence: 73%
“…Bemis et al 12) reported that 260 Db decays with a half-life of 1:52 AE 0:13 s, three values of 9.041, 9.074, and 9.120 MeV for decay, and a 9.6% spontaneous-fission branch.…”
Section: Decay Property 411 Decay Of 260 Dbmentioning
confidence: 98%